War and national memory: Georgian, Polish, and British perspectives - Lily Hamourtziadou; Przemyslaw Lukasik; Khatuna Chapichadze (Journal of Global Faultlines)
Essentialist understandings of ethnicity and nationhood suggest that ethnic or national identities are set in stone and hence immutable, but we argue that they are continuously developed into existence through past and present narratives, as they are articulated through historical accounts, national myths, and stories of the dead. The most emotionally powerful symbols of historical memory supporting such narratives are war memorials and museums, where the nation’s dead are remembered. We explore the ways in which human war casualties are remembered – and not remembered – through the study of memorials and museums in three different national contexts: in Georgia, in Poland, and in Great Britain.